ENVIRONMENTAL ADAPTATION OF UPLAND INDIGENOUS PEOPLES IN THE PHILIPPINES: BASIS FOR LOCAL RESILIENCE TO CLIMATE CHANGE - Campos, Maria Rebecca A (PEOPLE: International Journal of Social Sciences, 2019)
The study dealt with the literary works of Ifugaos, upland indigenous peoples in the Philippines to describe their environmental adaptation as basis for local resilience to climate change. It focused on their beliefs, traits and values; their approach and prevailing practices to environment with its strengths and weaknesses; their adaptive management in response to environmental conditions; and from the findings the local resilience strategy framework to climate change was established. The study used qualitative descriptive method which was narrative in nature using literary analysis. The use of spiritual beliefs, rituals and ceremonies; ecological wisdom; forest protection; kinship orientation; sense of tribal awareness and peace pacts; artistic in temperament; and survival as manifested in their literary works were the approach and prevailing practices to environment of the indigenous peoples. The strengths and weaknesses of their beliefs, traits, values, practices and subsistence; and the adaptation process of their adaptive management and community were the bases of local resilience strategy to climate change. The heritage of the indigenous peoples in terms of effective and efficient environmental adaptation should be preserved and dignified by all sectors of the society. Ecological wisdom, forest protection and resourcefulness should be practiced by all. These practices should be integrated in environmental awareness with public dissemination of information and documentation to be initiated by environmental agencies and educational institutions. The Philippine government and non-governmental organizations should enrich the strengths of the indigenous peoples in terms of environmental adaptation; and initiate projects that will improve the modes of subsistence and knowledge; and reduce the beliefs in super natural, heavy dependence on physical environment, conservatism and shyness of the indigenous peoples. The strategy framework to climate change for local resilience is proposed and highly recommended to all institutions and communities concerned for environmental adaptation to climate change.